Bojongmanik Formation Sedimentation Mechanism in the Middle to Late Miocene (N9-N17) in the Rangkasbitung Basin - Tety Syahrulyati; Vijaya Isnaniawardhani; Mega Fattima Rosana; Winantris Winantris (Testing Center for Oil and Gas LEMIGAS, 2020)
The Rangkasbitung Basin, is a part of Banten Depression which was formed by a normal fault, and then fi lled by marine deposits. This research carried out to understand the sedimentation process of Middle Miocene Bojongmanik deposits, the age, paleoenvironment and lithology (sediment sequence). In this research, 55 samples were taken from the study area, approximately 595 km2. Measurement of the stratigraphic section is carried out to determine the correlation both vertically and horizontally. The residue of dissolving peroxide method was carried out during the samples preparation. Then genus and species of planktonic and benthonic foraminifera were identifi ed and determined. The foraminifera analysis guide has been used to determine the age and depositional environment. The sequences of Bojongmanik Formation were deposited in Middle to Upper Miocene (N9 to N17). Based on the planktonic foraminifera distribution, the succession of each sequence can be correlated. During Middle Miocene (N9 - N12), the lowest part of Bojongmanik Formation is deposited at 100m-200m and 100m-80m depth, while in the other site, the correlated sequence is recorded that deposited at 80m-20m depth (outer to edge of inner neritic facies). In late Middle Miocene (N13 - N14), the regression process was happened. Almost the succession was deposited on land, while in deep site, a less part of sediments was formed as land facies but the most of it deposited as marine facies. In Upper Miocene (N 15 - N 17), the sedimentation continued in the transitional to edge neritic in back mangrove to mangrove environmental setting (upper to lower delta plain), and in other sites the sediment is no longer formed. Based on distribution of benthonic foraminifera there are observed the biofacies changes laterally. In bathymetric of depositional environment maps it can be depicted two higher paleoenvironmental sites (Cigudeg and Muncang highs) and two lower sites (Leuwiliang and Jasinga basins).